2018
DOI: 10.22159/ijap.2018v10i2.24174
|View full text |Cite
|
Sign up to set email alerts
|

Design, Formulation and Evaluation of Liposome Containing Isoniazid

Abstract: Objective: The objective of the present study was to formulate and evaluate liposomes loaded with isoniazid.Methods: Liposome of isoniazid was made by thin layer film hydration method. L-α-phosphatidylcholine and cholesterol were used to make multiamellar vesicles. Six batches of liposomes were prepared based on the different weight ratio of L-α-phosphatidylcholine and cholesterol. Differential scanning calorimetry (DSC) study conducted to study in any incompatibility.Results: The prepared liposomes were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The encapsulation efficiency of the liposomes was calculated as: EE % = [(Amount of drug entrapped in liposome/Total amount of drug taken initially) × 100]. 27…”
Section: Determination Of Proteins Peptides Mgo and Their Mixture Enc...mentioning
confidence: 99%
“…The encapsulation efficiency of the liposomes was calculated as: EE % = [(Amount of drug entrapped in liposome/Total amount of drug taken initially) × 100]. 27…”
Section: Determination Of Proteins Peptides Mgo and Their Mixture Enc...mentioning
confidence: 99%
“…One method is loading liposomes with isoniazid. According to a study by Roy et al, liposomes of isoniazid, which are made by thin-layer film hydration, showed entrapment efficiency, which was determined by the particle sizes viewed from scanning electron microscopy (SEM) photographs [63]. The process involved the use of isoniazid or soya lecithin (L-a-phosphatidylcholine) and chloroform.…”
Section: Soy Lecithin-derived Liposome (Slp): From Competitive Advmentioning
confidence: 99%
“…Furthermore, when stored at low temperatures and light preservation, liposomes can avoid the reactions. Moreover, isoniazid liposomes were associated with proper entrapment and stability due to pH adjustments, temperature, ionic interaction, and application of cholesterol in the bilayer structure [63]. Therefore, loading liposomes with isoniazid can be used to solve entrapment issues with liposomes.…”
Section: Soy Lecithin-derived Liposome (Slp): From Competitive Advmentioning
confidence: 99%
“…To produce cyphetrylin liposomes, we used the Bangham method [15]. Cyphetrylin substance and lipid components (SPC, cholesterol, and PEG-DSPE) were dissolved in chloroform.…”
Section: Production Of Liposomes With Cyphetrylinmentioning
confidence: 99%